Decolonial pedagogical practices: Engaging with Rancière - Postma, D.J.v.R (South African Journal of Higher Education, 2019)
The 2015/6 student protests in South Africa questioned the 1994 postcolonial settlement by drawing attention to the demands of decoloniality. The processes of decoloniality are characterised by an openness to pedagogies, epistemologies and forms of governance that promote a plurality of becomings. In order to investigate how educational practices could contribute towards decoloniality, this article draws on Rancière’s notion of ‘equal intelligence’. It is argued that this notion of radical equality could assist educators to redefine themselves and their role in emancipatory and decolonial education. This role avoids the extremes of the authoritarian educator on the one hand, and the egalitarian educator, on the other. ‘Equal intelligence’ makes possible a pedagogical space which demands of the student to use his/her intelligence to generate knowledge that does not reproduce a hegemonic tradition. Equality is not the result of an educational intervention, but a presumption that shapes the pedagogical relation as such. This applies also to decolonisation: The presumption of equal intelligence is a powerful way to decolonise the mind. In this process the educator has an important role to play to create a context  where the will and the freedom to participate in the construction of powerful knowledge is kept alive.